Development of microsatellite markers for Helopeltis theivora waterhouse (Hemiptera: Miridae) - Md Latip, Siti Noor Hajjar; Muhamad Awang, Rita; Gnanasegaram, Manjeri; Tan, Soon Guan (Academic Journals, 2010)
Helopeltis theivora is an important pest of cocoa, tea, mangoes and ornamental plants in Asia. In the effort to control this insect pest effectively, information on its population genetics is needed. Single locus DNA microsatellites are very efficient in being able to provide such information when they are used in the study of the population structures of organisms as they are co-dominant markers. As no such marker is available for this species yet, here we reported in our work, the isolation and development of six of such markers which were found to be polymorphic when tested on samples from three populations of this insect in Peninsular Malaysia.